A Note on Technical Change, Skill Formation, and Economic Instability*. Issue 1 (2nd January 2020) - Bina, Cyrus
Abstract: Skill formation in advanced capitalism is a theme that has long been the subject of economic theory. The contention here is that neither the orthodoxy nor heterodoxy allows for a consistent theory of skill formation germane to capitalism proper. Neoclassical theory treats labor and thus skills along the "aggregate production function"/factor-of-production theory. Neo-Marxian view (á la Braverman) identifies skills with crafts and thus aims at deskilling. Nevertheless, despite the elegant mathematical style ascribed to the former and the sophisticated rhetoric accredited to the latter, these competing schools had not yet offered a sui generis notion of skill formation aimed at corporeality of capitalism. This article, by allowing for technical change and through the synthesis of "creative destruction and "destructive creation, " offers an indispensable theory of skill formation, away from Braverman's craft-centric method, and beyond eclecticism, skillset fetishism, and human-capital essentialism omnipresent in both orthodox and heterodox literature.